The Perfect Match: Testing the Effect of Increasing Red and Blue Ratio on Baby-Leaf Kale Growth, Yield and Physiology - Ilaria Zauli; Ernesto Rossini; Giuseppina Pennisi; Michael Martin; Andrea Crepaldi; Giorgio Gianquinto; Francesco Orsini (Horticulturae)
Within the current scenario of cropland use and forest surface loss, there is a need for the implementation of viable urban farming systems, e.g., indoor vertical farming (VF). Light management is fundamental in VF, although responses to light spectra are often species-specific. As the interest of consumers and farmers towards baby-leaf vegetables has recently increased, this study aimed at assessing the most effective red:blue (RB) ratio for enhanced baby-leaf production of kale (Brassica oleracea). Within an ebb-and-flow system, increasing RB ratios (RB3, RB5, RB7 and RB9) were tested, sharing a photoperiod of 16 h day−1 and a light intensity of 215 μmol m−2 s−1. A larger yield was obtained for plants under RB5, featuring an intermediate B fraction compared to other treatments, with plants displaying more expanded and thinner leaves. Also, for lighting energy and cultivated surface use efficiency, RB5 was the most effective treatment, performing up to 57 g FW kWh−1 and 54 kg FW m−2 y−1, respectively. From multispectral data, a tendency of reduced Fv/Fm and Fq′/Fm′ was observed as the RB ratio increased, while the chlorophyll index was enhanced under RB ≥ 7. This study highlighted the light recipe with an RB ratio of 5 as the most effective lighting mixture for optimal baby-leaf kale production in terms of balanced growth, resource use efficiency and yield.